COMPARISON OF SERUM TESTOSTERONE LEVELS AMONG STUDENTS STUDYING IN RELIGIOUS INSTITUTIONS AND NON-RELIGIOUS INSTITUTIONS - Khattak, Naheed; Habib, Syed Hamid; Rahman, Ubaid ur; Zeeshan, Noreen; Gul, Seema (Journal of Ayub Medical College Abbottabad, 2020)
Background: Testosterone levels are shown to be affected by the social environment where individuals spend most of the duration of their daily activities. It has been reported that religion may play a role in reducing harm and contributing to the resilience of young people. The objective of the study was to compare the serum Testosterone level of College students with that of the Madrassa students of the same age group. Methods: This was a cross-sectional study with a total of 145 participants between 18-25 years of age. Subjects from the religious institutions (Madrassa) were 30 and non- religious institutions (Colleges) were 115. Fasting blood samples were obtained from all participants for serum testosterone levels (measured using Radioimmunoassay (RIA) technique). Results: Students studying in religious institutions (Madrassa) have significantly (p=0.001) lower serum Testosterone (6.5±2.01 ng/ml) levels compared to students of the non-religious institution, i.e., 9.08±3.07 ng/ml. Conclusion: The social environment of studies like madrassa or college affects testosterone hormone levels. Keywords: Serum testosterone levels; Religious institutions; Madrassa